Design and analysis of an UTeM antenna - Dalila, Misman; Mohamad Zoinol A., Abdul Aziz; Soh, Ping Jack; R. Badlishah, Ahmad, Assoc. Prof. Dr. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/